Synthesis and application of silica based mesoporous materials for removal of endocrine disrupting compounds in aqueous solution / Shanmuga Suntharam Kittappa - Shanmuga Suntharam , Kittappa (2015)
The economical synthesis route of silica based mesoporous materials using eco-friendly and cheaper chemicals and material was studied. Three mesoporous silica-based materials were successfully synthesized and applied for the removal of endocrine disrupting compounds (EDCs): mesoporous silica materials (MSMs) synthesized by reacting pore templating agent Pluronic P123® with silica (SiO2) powder instead of organometallic precursors [i.e. tetraethyl orthosilicate (TEOS)]; magnetised nanocomposite silica material (MNCM) synthesized by incorporating MSMs with nano magnetite; and N1-(3-Trimethoxysilylpropyl) diethylenetriamine (Tris) coated magnetised nanocomposite silica materials (MNCMT) synthesized by incorporating MNCM with Tris. The synthesized materials were characterized by X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET)/Barrett-Joyner-Halenda (BJH) surface and pore size distribution analysis, fourier transform infra-red spectroscopy (FTIR), magnetometer, zetasizer, field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). In the first phase, MSMs were synthesized at different calcination temperatures and tested for the removal and drug loading capacities of ibuprofen (IBP). The results of isotherms and kinetics of IBP removal indicated that MSM calcined at 500 oC (MSM500) had the highest sorption capacity and speed than other MSMs, SBA15 and zeolite. The IBP removal mechanism was identified as a hydrophilic interaction between the carboxylic group (COO–) of IBP and silanol (Si–OH) of the pore surface. In the second phase, to further improve the separation process, MNCMs were prepared using SiO2 and nano-magnetite (Fe3O4) via a new synthetic route, and applied to remove methylene blue (MB). Among the synthesized materials (MNCM-0.25, -0.5 and -1),iv MNCM-1 was found to have the magnetic property (2.9 emu/g) and highly sharp pore size distribution. It also had high and fast adsorptive ability to remove MB. The removal of MB by MNCM-1 is a physisorption process and thermodynamically favourable at higher temperatures. The process involves an electrostatic interaction between negatively charged silanol (Si-O-) and positively charged MB. Conversely, the removal of other EDCs such as BPA, CFA and IBP with MNCM-1 was not very effective. In the third phase, MNCM was functionalized by incorporating 1 mmol, 2 mmol and 3 mmol of N1-(3-Trimethoxysilylpropyl) diethylenetriamine (Tris), and the products were denoted as MNCMT-1, -2 and -3, respectively. The synthesized MNCMTs products were used to remove ibuprofen (IBP), bisphenol A (BPA) and clofibric acid (CFA). Whilst, the resulting MNCMT-3 revealed the highest adsorption capacity (182 mg/g) for the removal of BPA followed by MNCMT-2 and -1, MNCMT-1 was demonstrated to have higher adsorption capacity than MNCMT-2 and -3 for IBP and CFA. The removal mechanism of BPA, IBP and CFA was influenced by the hydrophobicity behaviour and the surface charge of MNCMT, which was dominantly affected by the  hydrogen bonding between the adsorbate and adsorbent. A cost analysis study revealed that MSM, MNCM and MNCMT were much cheaper than any other mesoporous silica material for the removal of EDCs.